The Relationship of Some Aspects of Upbringing Style With Preschool Children’s Behaviour - Dženan Skelić (Društvene i Humanističke Studije, 2018)
The research deals with the relationship between an educational style which parents prefer and someelements of their children’s behavior in a preschool educational facility. Some of the methods used werea descriptive-analytic survey method and some of the techniques: surveys and tests. Among some ofthe instruments there were: an educational style scale, a flexibility test and an observational list withmultiple-choice answers. The sample involved with 44 preschool children, their parents and 5 teachersin preschools. The research showed that educational styles preferred by the preschool children’s familiesis not a significant factor in determining the behavioral patterns of the children, neither is an absence oftheir flexibility. Factors which did matter was the educational background of their mothers and thefinancial status of their families.